Digital Transformation in the Luxury Industry: Louis Vuitton's Strategic Response and Innovation - Zheng, Anqi (Transactions on Economics, Business and Management Research, 2024)
The study seeks to examine the ways in which luxury businesses, including Louis Vuitton, enhanced their marketing methods in response to the difficulties posed by the pandemic. This paper aims to analyze the influence of these techniques on brand recognition, consumer involvement, and sales effectiveness across several stages of the epidemic. During these time periods, this paper also witnesses the transition from traditional in-person shopping to online shopping, as well as the use of advanced digital technologies like Virtual Reality (VR), Augmented Reality (AR), and Artificial Intelligence (AI) in marketing strategies. This research has revealed that digital transformation plays a crucial role in preserving market position and fostering client loyalty. This article proposes recommendations for LV's future trajectory in light of its current condition, which entail increasing expenditures in technology and revising its initial digitalization approach. Enhanced integration of nascent technologies can propel the organization to greater heights, ensuring it remains inventive and adaptable, better satisfying the demands of consumers, the market, and the current era.